Controlled weakening of model ice: Replicating the mechanical response of summer-warmed sea ice in laboratories and test basins - N. Fuchs; F. von Bock und Polach; P. Buil; S.M. Isay; D. Notz; L. Nupnau; N. Reimer; L. Schoepflin; T. Zorn (Ocean Engineering, 2026)

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Toluene photo-oxidation and secondary organic aerosol formation: EUROCHAMP-2020 multi-chamber experiments - Petro Uruci; Kalliopi Florou; Marco Paglione; Christos Kaltsonoudis; Bénédicte Picquet-Varrault; Jean-François Doussin; Mathieu Cazaunau; Ari Leskinen; Liqing Hao; Annele Virtanen; David M. Bell; Anke Mutzel; et al. (Journal of Atmospheric Chemistry, 2025)

Didesmethylrocaglamide cytotoxic activity in high grade serous ovarian cancer in preclinical in vitro and in vivo models - Elizabeth N. Kaweesa; Tyler A. Wilson; Jaqueline M. Bazioli; Li Pan; A. Douglas Kinghornb James R. Fuchs; Joanna E. Burdette (Phytochemistry Letters, 2025)

Didesmethylrocaglamide Cytotoxic Activity in High Grade Serous Ovarian Cancer in Preclinical In Vitro and In Vivo Models - Elizabeth N. Kaweesa; Tyler A. Wilson; Jaqueline M. Bazioli; Li Pan; A. Douglas Kinghorn; James R. Fuchs; Joanna E. Burdette (Phytochemistry Letters, 2025)

Antibacterial Synergism of Fluoxetine and Paroxetine with Ceftriaxone, Plasmid DNA Cleavage and Repositioning - Vitória S. Foletto; Marissa B. Serafin; Augusto D. da Mota; Taciéli F. da Rosa; Angelita Bottega; Sara L. Marion; Bruno R. de Paula; Laísa N. Franco; Luana B. Fuchs; Rosmari Hörner (Current Microbiology, 2025)

Mixture toxicity study of two metal oxide nanoparticles and chlorpyrifos on Eisenia andrei earthworms - Marcela I. Cáceres-Wenzel; Florencia N. Bernassani; Julio S. Fuchs; Eduardo Cortón; Adriana C. Cochón (Environmental Science and Pollution Research, 2024)

Repositioning of Benzodiazepine Drugs and Synergistic Effect with Ciprofloxacin Against ESKAPE Pathogens - Taciéli F. da Rosa; Marissa B. Serafin; Vitória S. Foletto; Laísa N. Franco; Bruno R. de Paula; Luana B. Fuchs; Luciano Calegari; Rosmari Hörner (Current Microbiology, 2023)

A desiccated dual-species subaerial biofilm reprograms its metabolism and affects water dynamics in limestone - F. Villa; N. Ludwig; S. Mazzini; L. Scaglioni; A.L. Fuchs; B. Tripet; V. Copié; P.S. Stewart; F. Cappitelli (Science of The Total Environment, 2023)

Lipid droplets and perilipins in canine osteosarcoma. Investigations on tumor tissue, 2D and 3D cell culture models - N. Leitner; J. Hlavatý; R. Ertl; S. Gabner; A. Fuchs-Baumgartinger; Ingrid Walter (Veterinary Research Communications, 2022)
Lipid droplets were identified as important players in biological processes of various tumor types. With emphasis on lipid droplet-coating proteins (perilipins, PLINs), this study intended to shed light on the presence and formation of lipid droplets in canine osteosarcoma. For this purpose, canine osteosarcoma tissue samples ( n = 11) were analyzed via immunohistochemistry and electron microscopy for lipid droplets and lipid droplet-coating proteins (PLINs). Additionally, we used the canine osteosarcoma cell lines D-17 and COS4288 in 2D monolayer and 3D spheroid (cultivated for 7, 14, and 21 days) in vitro models, and further analyzed the samples by means of histochemistry, immunofluorescence, molecular biological techniques (RT-qPCR, Western Blot) and electron microscopical imaging. Lipid droplets, PLIN2, and PLIN3 were detected in osteosarcoma tissue samples as well as in 2D and 3D cultivated D-17 and COS4288 cells. In spheroids, specific distribution patterns of lipid droplets and perilipins were identified, taking into consideration cell line specific zonal apportionment. Upon external lipid supplementation (oleic acid), a rise of lipid droplet amount accompanied with an increase of PLIN2 expression was observed. Detailed electron microscopical analyzes revealed that lipid droplet sizes in tumor tissue were comparable to that of 3D spheroid models. Moreover, the biggest lipid droplets were found in the central zone of the spheroids at all sampling time-points, reaching their maximum size at 21 days. Thus, the 3D spheroids can be considered as a relevant in vitro model for further studies focusing on lipid droplets biology and function in osteosarcoma.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Metagenomic analysis of nepoviruses: diversity, evolution and identification of a genome region in members of subgroup A that appears to be important for host range - J. M. Hily; N. Poulicard; J. Kubina; J. S. Reynard; A. S. Spilmont; M. Fuchs; O. Lemaire; E. Vigne (Archives of Virology, 2021)
Data mining and metagenomic analysis of 277 open reading frame sequences of bipartite RNA viruses of the genus Nepovirus , family Secoviridae , were performed, documenting how challenging it can be to unequivocally assign a virus to a particular species, especially those in subgroups A and C, based on some of the currently adopted taxonomic demarcation criteria. This work suggests a possible need for their amendment to accommodate pangenome information. In addition, we revealed a host-dependent structure of arabis mosaic virus (ArMV) populations at a cladistic level and confirmed a phylogeographic structure of grapevine fanleaf virus (GFLV) populations. We also identified new putative recombination events in members of subgroups A, B and C. The evolutionary specificity of some capsid regions of ArMV and GFLV that were described previously and biologically validated as determinants of nematode transmission was circumscribed in silico . Furthermore, a C-terminal segment of the RNA-dependent RNA polymerase of members of subgroup A was predicted to be a putative host range determinant based on statistically supported higher π (substitutions per site) values for GFLV and ArMV isolates infecting Vitis spp. compared with non- Vitis -infecting ArMV isolates. This study illustrates how sequence information obtained via high-throughput sequencing can increase our understanding of mechanisms that modulate virus diversity and evolution and create new opportunities for advancing studies on the biology of economically important plant viruses.

Complex interactions with nutrients and sediment alter the effects of predation on a reef‐building coral - Mallory M. Rice; Daniel G. Baldwin; Janine N. Fischer; Corinne Fuchs; Deron E. Burkepile (Marine Ecology, 2021)
Framework‐building corals create the three‐dimensional structure of coral reefs and are subject to predation from fishes, echinoderms, and gastropods. Anthropogenic stressors can magnify the effects of such top‐down pressure on foundation species. The gastropod Coralliophila violacea (Kiener, 1836) depletes coral energy reserves via predation, potentially increasing coral susceptibility to land‐based pollution (i.e., sediment accumulation and nutrient pollution). We hypothesized that sedimentation would worsen coral mortality, while nutrient enrichment would mitigate the harmful effects of sediment and predation on coral mortality by increasing the densities of algal symbionts. To test these hypotheses, we conducted in situ surveys of the fringing reefs in Mo'orea, French Polynesia to explore the relationships among massive Porites spp . cover, C. violacea densities, and sediment accumulation on coral colonies across low and high nutrient sites. We also conducted a factorial field experiment to test the interactions among these stressors on coral tissue mortality, symbiont densities, and chlorophyll. Massive Porites colonies at higher nutrient sites had C. violacea densities 13 times higher than at low nutrient sites but there was no difference in the amount of live tissue on coral colonies with or without snails among these sites. In our experiment, there were interactions between predation and nutrients as well as nutrients and sediment that impacted coral mortality. Sedimentation and predation by C. violacea increased coral tissue mortality independently by ~20%. Nutrient enrichment reduced this effect in corals under sedimentation or predation pressure by lowering coral tissue mortality by 18% and increasing algal symbiont densities by ~28%. Our results indicate that sediment does not magnify top‐down pressure on this coral, and that moderate nutrient enrichment may interact with predation in complex, unexpected ways to alter the responses of corals to top‐down pressure.

Photosymbiose — neuartige Anwendungen in der Biomedizin - Myra N. Chávez; Benedikt Fuchs; Jörg Nickelsen (BIOspektrum, 2021)
We have recently proposed a novel strategy named photosynthetic tissue engineering to overcome clinical problems due to hypoxia. The idea is based on transgenic photoautotrophic microorganisms that produce oxygen and at the same time secrete functional recombinant proteins into tissues. In particular, the unicellular green alga Chlamydomonas reinhardtii has successfully been used to boost the regenerative potential of several biomedical devices, such as dermal scaffolds and surgical sutures.

Combined effects of goethite nanoparticles with metallic contaminants and an organophosphorus pesticide on Eisenia andrei - Marcela I. Cáceres-Wenzel; Julio S. Fuchs; Florencia N. Bernassani; Adriana C. Cochón (Environmental Science and Pollution Research, 2020)

Journal Club - Wolfgang Wohlleben; Jochen Graw; Roland Benz; Johannes Sander; Jonathan Wolf Mueller; Christoph von Ballmoos; Miriam Herbert; Daniela Kruck; Martin Thanbichler; Gottfried Wilharm; Kai Thormann; Thilo M. Fuchs; et al. (BIOspektrum, 2020)

In-situ-Untersuchung von Austenitkornwachstumsprozessen in Stählen mittels Hochtemperatur-Laser-Scanning-Konfokal-Mikroskop - N. Fuchs; C. Bernhard (BHM Berg- und Hüttenmännische Monatshefte, 2019)

Characteristics of meiofauna in extreme marine ecosystems: a review - Daniela Zeppilli; Daniel Leduc; Christophe Fontanier; Diego Fontaneto; Sandra Fuchs; Andrew J. Gooday; Aurélie Goineau; Jeroen Ingels; Viatcheslav N. Ivanenko; Reinhardt Møbjerg Kristensen; Ricardo Cardoso Neves; Nuria Sanchez; et al. (Marine Biodiversity, 2018)

The Arnon–Buchanan cycle: a retrospective, 1966–2016 - Bob B. Buchanan; Reidun Sirevåg; Georg Fuchs; Ruslan N. Ivanovsky; Yasuo Igarashi; Masaharu Ishii; F. Robert Tabita; Ivan A. Berg (Photosynthesis Research, 2017)

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

Approach to Cerebrospinal Fluid (CSF) Biomarker Discovery and Evaluation in HIV Infection - Richard W. Price; Julia Peterson; Dietmar Fuchs; Thomas E. Angel; Henrik Zetterberg; Lars Hagberg; Serena Spudich; Richard D. Smith; Jon M. Jacobs; Joseph N. Brown; Magnus Gisslen (Journal of Neuroimmune Pharmacology, 2013)

An additional substrate binding site in a bacterial phenylalanine hydroxylase - Judith A. Ronau; Lake N. Paul; Julian E. Fuchs; Isaac R. Corn; Kyle T. Wagner; Klaus R. Liedl; Mahdi M. Abu-Omar; Chittaranjan Das (European Biophysics Journal, 2013)

Holocene river and slope activity in the Visoko Basin, Bosnia‐ H erzegovina – climate and land‐use effects - S. DREIBRODT; C. LUBOS; R. HOFMANN; N. MÜLLER‐SCHEEßEL; I. RICHLING; O. NELLE; M. FUCHS; K. RASSMANN; Z. KUJUNDŽIĆ‐VEJZAGIĆ; H.‐R. BORK; J. MÜLLER (Journal of Quaternary Science, 2013)
Alluvial and colluvial deposits were investigated at prehistoric tells close to the Bosna River. The chronology is based on ten radiocarbon ages, five optically stimulated luminescence ages, and on the archaeological record. Fluvial activity of the Bosna River is indicated by overbank fines [ca. 5000 (±1000) BC , 500 BC until today] and a phase of lateral displacement of the river bed with subsequent channel fills ca. 2000–500 BC . Early Holocene fluvial activity was probably triggered by climatic variability but might have promoted the expansion of Neolithic societies into the Visoko Basin. Mid‐ to late Holocene river activity occurred under increased climatic aridity but coincided with the expansion of prehistoric settlements to a wider area of the river basin on hard rocks in the adjacent mountainous areas. The destruction of the thin soil cover in the mountains is discussed as a probable trigger for enduring subsequent river activity. This is also indicated by a change in the geochemical signature of the alluvial sediments. The proposed mechanism might explain the mid to late Holocene river history in other regions. The potential of geochemical analyses and diachronous high‐resolution archaeological records to make inferences regarding sediment sources and geomorphological processes is demonstrated. Copyright © 2013 John Wiley & Sons, Ltd.

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Chemical composition of tourmaline from the Asarcık Pb–Zn–Cu ± U deposit, Şebinkarahisar, Turkey - F. Yavuz; Y. Fuchs; N. Karakaya; M. Ç. Karakaya (Mineralogy and Petrology, 2008)

Flow cytometric measurements do not reveal different ploidy levels in Minthostachys (Lamiaceae) - A. N. Schmidt-Lebuhn; J. Fuchs; M. Kessler (Plant Systematics and Evolution, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Ecotoxicological Characterization of a Disposal Lagoon from a Munition Plant - J. S. Fuchs; M. L. Oneto; N. B. Casabé; O. Gómez Segura; R. Tarulla; M. Vaccarezza; C. Sánchez-Rivas; E. M. Kesten; E. J. Wood (Bulletin of Environmental Contamination and Toxicology, 2001)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Differential effects of 7-OH-DPAT on amphetamine-induced stereotypy and conditioned place preference - T. V. Khroyan; D. A. Baker; R. A. Fuchs; N. Manders; J. L. Neisewander (Psychopharmacology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)